Finská romština - gramatický náčrt - Granqvist, Kimmo (Romano džaniben, 2012)
In my paper, I will present a concise grammar of Finnish Romani. I will present a short sketch of phonological system. The focus on this paper is on noun and verb morphology in contemporary spoken Romani. Emphasis is on variation and language change in a situation, where the dialect is little used and a lot of variation is permitted, and virtually all speakers’ dominating language is Finnish. Some of the most salient contact-induced changes are discussed, including the imposition of Finnish phonological rules, the use of Finnish cases and tenses, and the replication of Finnish morphosyntax using mainly the own resources of the dialect.